2019
DOI: 10.3390/v11040380
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of EIAV env Quasispecies during Long-Term Passage In Vitro: Gradual Loss of Pathogenicity

Abstract: As the only widely used live lentiviral vaccine, the equine infectious anima virus (EIAV) attenuated vaccine was developed by in vitro passaging of a virulent strain for 121 generations. In our previous study, we observed that the attenuated vaccine was gradually selected under increased environmental pressure at the population level (termed a quasispecies). To further elucidate the potential correlation between viral quasispecies evolution and pathogenesis, a systematic study was performed by sequencing env u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Previous research using sequencing techniques revealed that the diversity of the attenuated EIAV vaccine was four times higher than its parent strain (Figure S1). Furthermore, a clear parallel was found between the increased diversity and the increased passaging in vitro during the developing attenuation of virulent strain [ 10 ]. Here, three EIAV strains supposedly varying in env diversity were constructed, including an attenuated vaccine EIAV_HD, a recombinant strain EIAV_MD, and a monoclonal infectious clone EIAV_LD ( Figure 1 (A)) (details are given in materials and methods) [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research using sequencing techniques revealed that the diversity of the attenuated EIAV vaccine was four times higher than its parent strain (Figure S1). Furthermore, a clear parallel was found between the increased diversity and the increased passaging in vitro during the developing attenuation of virulent strain [ 10 ]. Here, three EIAV strains supposedly varying in env diversity were constructed, including an attenuated vaccine EIAV_HD, a recombinant strain EIAV_MD, and a monoclonal infectious clone EIAV_LD ( Figure 1 (A)) (details are given in materials and methods) [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Systematic sequencing analysis showed that the genomic diversity of the attenuated vaccine EIAV DLV121 was 2.5 times higher than that of its parental strain (2.07% vs 0.81%). Our previous studies suggested that the vaccine EIAV DLV121 might be evolved from a natural quasispecies [2,3,10]. Such intriguingly high diversity in the EIAV DLV121 vaccine was perhaps acquired through an evolutionary process during the long-time passaging.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Unlike hosts with infections caused by other lentiviruses, most horses infected with EIAV become lifelong inapparent EIAV carriers by eliciting immune control over virus replication [3][4][5]. An attenuated EIAV vaccine was developed through long-term passaging in equine macrophages in vitro and has successfully controlled the EIA epidemic in China, indicating that protective immunity can be induced after virus infection [5][6][7]. EIAV has therefore been widely accepted as a system for identifying potential immune control over lentiviruses [1,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike hosts with infections caused by other lentiviruses, most horses infected with EIAV become lifelong inapparent EIAV carriers by eliciting immune control over virus replication [3][4][5]. Additionally, an attenuated EIAV vaccine was developed through longterm passaging in equine macrophages in vitro and has successfully controlled the EIA epidemic in China, indicating that protective immunity can be induced after virus infection [5][6][7]. EIAV has therefore been widely accepted as a system for identifying potential immune control over lentiviruses [1,8,9] .…”
Section: Introductionmentioning
confidence: 99%